2018
DOI: 10.3389/fpsyt.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial with e-MotionalTraining® 1.0 for Social Cognition Rehabilitation in Schizophrenia

Abstract: BackgroundSchizophrenia patients present deficits in social cognition (SC), emotion and social perception, theory of mind (ToM), and attributional style. This study tested the efficacy, in real clinical conditions, of a online self-training program in SC, e-Motional Training®, in comparison with treatment as usual.MethodA randomized single-blinded multicenter clinical trial was conducted with 60 schizophrenia stable outpatients. All patients (control and intervention) were treated with drug therapy, case manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 76 publications
3
6
0
Order By: Relevance
“…The meta-analysis included 58 studies, Bell, Fiszdon, Greig, Wexler, and Bryson (2007), Bell, Zito, Greig, and Wexler (2008), Bellucci, Glaberman, and Haslam (2003), Bryce et al (2018), Cavallaro et al (2009), Choi et al (2018), Contreras, Tan, Lee, Castle, and Rossell (2018), d'Amato et al (2011), Eack et al (2009), Fisher, Holland, Merzenich, and Vinogradov (2009), Fisher, Holland, Merzenich, and Vinogradov (2010), Fisher, Mellon, Wolkowitz, and Vinogradov (2016), Fisher et al (2015), Fiszdon, Kurtz, Choi, Bell, and Martino (2016), Garety et al (2015), Garrido et al (2013), Gottlieb et al (2017), Greig, Zito, Wexler, Fiszdon, and Bell (2007), Hogarty et al (2004), Hooker et al (2012), Iwata et al (2017), Jahshan, Vinogradov, Wynn, Hellemann, and Green (2019), Krzystanek, Borkowski, Skałacka, and Krysta (2019), Kukla, Bell, and Lysaker (2018), Kurtz, Mueser, Thime, Corbera, and Wexler (2015), Kurtz, Seltzer, Shagan, Thime, and Wexler (2007), Lado-Codesido, Méndez Pérez, Mateos, Olivares, and García Caballero (2019), Lee (2013), Leff, Williams, Huckvale, Arbuthnot, and Leff (2013), Lindenmayer et al (2018), Mahncke et al (2019), Maroño Souto et al (2018), Matsuda et al (2018), Miley et al (2020), Moritz et al (2011, 2015a, 2015b, 2016), Pitkänen et al (2012), Popov et al (2011, 2014), Rass et al (2012), Rodewald et al (2011), Sachs et al (2012), Schlosser et al (2018), Shuib, Ahmad, Osman, and Alwi (2019), Tessier et al (2020), Urben, Pihet, Jaugey, Halfon, and Holzer (2012), Van den Noortgate, López-López, Marín-Martínez, and Sánchez-Meca (2013), Vauth et al (2005), Vinogradov et al (2009), Vreeland et al (2006), Wölwer et al (2005), Xu et al (2019), and Zhu et al (2020) (online Supplementary Table S1) reporting 618 effect sizes or SMCs. The total sample comprised of 4394 participants, of whom 64.31% were male.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis included 58 studies, Bell, Fiszdon, Greig, Wexler, and Bryson (2007), Bell, Zito, Greig, and Wexler (2008), Bellucci, Glaberman, and Haslam (2003), Bryce et al (2018), Cavallaro et al (2009), Choi et al (2018), Contreras, Tan, Lee, Castle, and Rossell (2018), d'Amato et al (2011), Eack et al (2009), Fisher, Holland, Merzenich, and Vinogradov (2009), Fisher, Holland, Merzenich, and Vinogradov (2010), Fisher, Mellon, Wolkowitz, and Vinogradov (2016), Fisher et al (2015), Fiszdon, Kurtz, Choi, Bell, and Martino (2016), Garety et al (2015), Garrido et al (2013), Gottlieb et al (2017), Greig, Zito, Wexler, Fiszdon, and Bell (2007), Hogarty et al (2004), Hooker et al (2012), Iwata et al (2017), Jahshan, Vinogradov, Wynn, Hellemann, and Green (2019), Krzystanek, Borkowski, Skałacka, and Krysta (2019), Kukla, Bell, and Lysaker (2018), Kurtz, Mueser, Thime, Corbera, and Wexler (2015), Kurtz, Seltzer, Shagan, Thime, and Wexler (2007), Lado-Codesido, Méndez Pérez, Mateos, Olivares, and García Caballero (2019), Lee (2013), Leff, Williams, Huckvale, Arbuthnot, and Leff (2013), Lindenmayer et al (2018), Mahncke et al (2019), Maroño Souto et al (2018), Matsuda et al (2018), Miley et al (2020), Moritz et al (2011, 2015a, 2015b, 2016), Pitkänen et al (2012), Popov et al (2011, 2014), Rass et al (2012), Rodewald et al (2011), Sachs et al (2012), Schlosser et al (2018), Shuib, Ahmad, Osman, and Alwi (2019), Tessier et al (2020), Urben, Pihet, Jaugey, Halfon, and Holzer (2012), Van den Noortgate, López-López, Marín-Martínez, and Sánchez-Meca (2013), Vauth et al (2005), Vinogradov et al (2009), Vreeland et al (2006), Wölwer et al (2005), Xu et al (2019), and Zhu et al (2020) (online Supplementary Table S1) reporting 618 effect sizes or SMCs. The total sample comprised of 4394 participants, of whom 64.31% were male.…”
Section: Resultsmentioning
confidence: 99%
“…,Leff, Williams, Huckvale, Arbuthnot, and Leff (2013),Lindenmayer et al (2018),Mahncke et al (2019), Maroño Souto et al (2018,Matsuda et al (2018), Miley et al (2020,Moritz et al (2011Moritz et al ( , 2015aMoritz et al ( , 2015bMoritz et al ( , 2016,Pitkänen et al (2012),Popov et al (2011Popov et al ( , 2014, Rass et al (2012), Rodewald et al (2011), Sachs et al (2012), Schlosser et al (2018), Shuib, Ahmad, Osman, and Alwi (2019), Tessier et al (2020), Urben, Pihet, Jaugey, Halfon, and Holzer (2012), Van den Noortgate, López-López, Marín-Martínez, and Sánchez-Meca (2013), Vauth et al (2005), Vinogradov et al (2009), Vreeland et al (2006), Wölwer et al (2005), Xu et al (2019), and Zhu et al (2020) (online Supplementary Table…”
mentioning
confidence: 99%
“…the question was posed and it can be asked to the classroom allowing some debate to reach a consensus without being prompted by time constrictions. These modules were designed to improve the recognition of facial expressions of emotions in individuals with severe mental disorders, the selection and validation of the pictures as well as the usefulness of the program in patients with schizophrenia has been published elsewhere (Maroño Souto et al, 2018;Vázquez-Campo et al, 2016).…”
Section: Interventionmentioning
confidence: 99%
“…The results of the initial unblinded controlled pilot study demonstrated statistically significant improvements in both Emotion Recognition (ER) and ToM (29). The version 1.0 has proven its efficacy in a multicenter randomized clinical trial (RCT) (30) and version 2.0 of the program, developed since 2013, is now available (31). ET 2.0 increased the number of different models with photographs, the number of games and a new movie was included with actors called "The Surprise. "…”
Section: Introductionmentioning
confidence: 99%